Perceptions, Experiences, and Challenges of Physicians Involved in Dementia Care During the COVID-19 Lockdown in India: A Qualitative Study - Banerjee, Debanjan; Vajawat, Bhavika; Varshney, Prateek; Rao, TS Sathyanarayana (Frontiers in Psychiatry, 2021)
Introduction With 5.3 million people living with dementia in India and the pandemic wreaking havoc, dementia care has faced unique challenges during the outbreak, with reduced healthcare access, travel restriction, long-term lockdown and fear of hospitalization. We explored the experiences and barriers faced by the physicians involved in dementia care during the lockdown period. Methods A qualitative approach was used with purposive sampling. After an initial pilot, 148 physicians were included in the study. They were virtually interviewed in-depth based on a pre-designed semi-structured questionnaire, in areas related to tele-consultations, attributes related to dementia care, challenges faced and way forward. Interviews were recorded, transcribed and thematically analyzed using Nvivo-10 software. Triangulation, peer debriefing and respondent validation were used to ensure rigor. Results The overarching categories that emerged were ‘Tele-medicine as the future of dementia care in India’, ‘people living with dementia being uniquely susceptible to the pandemic with a triple burden of: age, ageism and lack of autonomy’ and ‘markedly reduced healthcare access in this population with significant mental health burden of caregivers’. The experiences of the physicians were categorized into their challenges during the lockdown period and perceptions related to specific facets of dementia care during the crisis. The general physicians expressed special ‘unmet needs’ of dementia-specific training and specialist collaboration. Most of the participants perceived ambiguity related to the newly released telepsychiatry guidelines. Conclusion Resource constraints and pandemic burden are currently high. This study looks at the “voices” of those actively providing dementia care during the ongoing crisis and to the best of our knowledge, is the first one from India to do so. Concurring with their experiences, PwD and their families are exposed to multiple vulnerabilities during COVID-19, need tailored care, especially at the primary healthcare level which includes general physicians. These relevant “voices” are discussed in light of the new tele-psychiatry guidelines and further optimization of dementia care in an aging India.